Responsive enforcement under the Chilean Consumer Protection Act - Soto Delgado, Pablo (2026)
This article assesses the institutional framework for regulatory enforcement of the Chilean Consumer Protection Act. To this end, the study adopts the theoretical model of responsive regulation as a parameter. The paper argues that Chile’s institutional design for consumer enforcement is only partially responsive and therefore requires reform if this model is to be fully consolidated.